Pathways in the molecular fragmentation for the C2H5OH/He electrical discharge. Issue 3 (3rd April 2019) - Gómez, A.; Reyes, P. G.; Martínez, H.; Vergara, J.; Torres, C.; Contreras, V.
ABSTRACT: This study focuses on the glow discharge generated with a gases mixture of Ethanol (C2 H5 OH) and Helium (He), at different concentrations maintained at a total pressure of 2.0 Torr. We used optical emission spectroscopy (OES) to analyze the discharge mixture at different concentrations of Helium. Single Langmuir probe data was used to determine the Electron Energy Distribution Function (EEDF). For the total C2 H5 OH/He mixture plasma concentrations, the EEDF has a Maxwellian distribution function. A decrease in He concentration results in significant changes in the EEDF, this behavior is related to the increase in the C2 H5 OH percentage must increase the energy loses of the electrons in the inelastic collision with C2 H5 OH producing a significant change in the EEDF, therefore, the EEDF pattern results in an increase of electron–molecule reaction rates. The rise in electron temperature for increasing Helium percentage is explained by the decreasing electron energy loss in the inelastic collisions with C2 H5 OH molecule. It observes a decrease of electron density ne as a function of the Helium percentage, which can be related to the ratio between ionization cross sections of Helium and C2 H6 O molecule. The active species are generated in the electron-molecule processes, which are associated with electron impact dissociation of C2 H5 OH and Helium electronic impact excitation in the gas phase. The emission optical spectra (OES) show changes in the intensity of the most important peaks of the plasma mixture, which indicates the dependence in the formation of the plasma as a function of the percentage of the gases. The changes in the intensities of the same observed species are due to different processes of excitation and ionization energies of the system, in addition to the increase of He metastable states He I. Hydrogen is the main product obtained from the decomposition of C2 H5 OH.